Psychological Resilience of Residents of Pre-Retirement Age in Southern Siberia - Frokol, Anna S. (2021)
The development of resistance to life phenomena or other social reactions is based on the study of social response, which can be considered as the basis for the functioning of the socio-economic system in crisis conditions. For residents of the pre-retirement age, this is more important, since the opportunity to actively influence their personal sources of income and the development of trajectories of personal development is being lost. The relevance of the study is conditioned by lack of methods that study the features of the psychological well-being of an individual in modern realities in psychological science. In this regard, the paper aims to research psychological well-being, which measures certain components, aspects, types, and levels of psychological well-being. To achieve this purpose, the following methods were used in the paper: theoretical (method of system analysis of theoretical scientific approaches and concepts); empirical (survey method, testing); statistical methods of data processing (correlation, factorial, multiple regression analyses), the method of qualitative data analysis. The authors show that a significant function of sustainability in the social environment allows to fully implement development programmes that are involved in the design of documents for socio-economic development. The paper proves that the necessity of forming such a response is based on the long-term impact of political, social, and economic crises. The practical significance of the study is determined by the fact that social response allows to ensure resilience not only for the generation that is moving away from active social life, but also to ensure the continuity of individual structures that need to be implemented to develop sustainability in the socio-economic environment